Editorial - Jörg Tremmel; Maria Lenk; Antony Mason; Markus Rutsche (Intergenerational Justice Review)
If you had to choose one moment in history in which to be born, and you didn’t know in advance whether you were going to be male or female, which country you were going to be from, what your status was, you’d choose right now.” This answer to his one-question test was used by Barack Obama in several of his speeches to demonstrate how humanity has made progress up until the present day. Is he right? Beyond asking people what their preferred birth year would be in the context of such a thought experiment, it is possible to compare the attractiveness of actual birth years (and thus epochs in which to lead one’s life) from official statistics. There are already a handful of indices which are, if recorded repeatedly, usable for measuring the changes in quality-of-life circumstances over time, and thus the “position” of succeeding generations in the course of history.